2021
DOI: 10.3390/brainsci11121620
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation, Loneliness and Generalized Anxiety: Implications and Associations during the COVID-19 Quarantine

Abstract: The COVID-19 pandemic has resulted in a predominantly global quarantine response that has been associated with social isolation, loneliness, and anxiety. The foregoing experiences have been amply documented to have profound impacts on health, morbidity, and mortality. This narrative review uses the extant neurobiological and theoretical literature to explore the association between social isolation, loneliness, and anxiety in the context of quarantine during the COVID-19 pandemic. Emerging evidence suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 90 publications
2
16
0
Order By: Relevance
“…Similarly, for future anxiety, with massive changes in social structures, ranging from job status to caregiving aspects due to the COVID-19 pandemic, people who are more anxious about their future tend to develop social anxiety, which is a perceived threat to interpersonal relations and highly associated with loneliness [ 52 , 53 , 54 , 55 ]. Regarding subjective health status, our results showed that people with poorer health conditions tended to suffer from loneliness, which aligns with findings from previous studies [ 29 , 56 ]. Finally, a myopic view of the future was another strong predictor of loneliness, especially among younger males.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, for future anxiety, with massive changes in social structures, ranging from job status to caregiving aspects due to the COVID-19 pandemic, people who are more anxious about their future tend to develop social anxiety, which is a perceived threat to interpersonal relations and highly associated with loneliness [ 52 , 53 , 54 , 55 ]. Regarding subjective health status, our results showed that people with poorer health conditions tended to suffer from loneliness, which aligns with findings from previous studies [ 29 , 56 ]. Finally, a myopic view of the future was another strong predictor of loneliness, especially among younger males.…”
Section: Discussionsupporting
confidence: 92%
“…Sex and self-reported disposable income were covariates in the model. also showed that loneliness was positively associated with anxiety and depression with significant path coefficients, adding to the ever growing literature that loneliness plays an important role in mental health conditions (Erzen and Çikrikci, 2018;Wilkialis et al, 2021). In addition, higher subjective social status also had a direct protective effect against anxiety and depression.…”
Section: Discussionmentioning
confidence: 56%
“…Common strategies to combat viral infections include quarantine and social isolation, which can cause mental and psychological disorders including acute and chronic stress, anxiety and depression ( Garcovich et al, 2020 ; Hwang et al, 2020 ; Pan et al, 2020 ; Wilkialis et al, 2021 ). These countermeasures are associated with sedentary behaviors that decrease physical exercise ( Booth et al, 2000 ; Lightfoot, 2011 ; Gasmi et al, 2020 ).…”
Section: The Concurrent Effects Of Covid-19 and Ms On Mental And Psyc...mentioning
confidence: 99%